Implementation of the Population Administration Service Program for Newborn Health Facilities at the Population and Civil Registration Office of Bandung City - Alamsyah Putra; Nandang Alamsah Deliarnoor; Antik Bintari (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study examines the implementation of the population administration service program related to newborn health facilities at the Population and Civil Registration Office (Disdukcapil) of Bandung City in 2024. Using Mazmanian and Sabatier’s policy implementation framework, this research analyzes three core dimensions: the tractability of the problem, the ability of the policy to structure implementation, and non-statutory variables affecting implementation. The study employs a qualitative descriptive method, with data collected through in-depth interviews, documentation, and field observations. The findings reveal three major issues: (1) difficulties in controlling implementation challenges due to actor diversity, uneven public awareness, and suboptimal data accuracy; (2) policy characteristics show inconsistency in coordination mechanisms, limited resource allocation, and underdeveloped technological integration; and (3) external environmental factors particularly socio-economic disparities, technological readiness, and institutional support significantly influence implementation outcomes. Strengthening inter-agency coordination and improving digital administration systems are essential to optimizing newborn registration services.